Relationship between estimated glomerular filtration rate and biological half-life of 131I - Vogel, K.; Opfermann, T.; Wiegand, S.; Biermann, J.; Busch, M.; Winkens, T.; Freesmeyer, M. (Nuklearmedizin - NuclearMedicine, 2013)
Aim: This retrospective study sought to investigate the relationship between biological half-life (t1/2 biol) of 131I and estimated glomerular filtration rate (eGFR) in patients with thyroid carcinoma. Patients, methods: 96 patients with differentiated thyroid carcinoma (69 women, 27 men, mean age 64.0 ± 13.6 years) and diagnostic and therapeutic administration of 131I were considered. Patients with pronounced specific iodine storage were not included in the study. The eGFR was estimated according to the Chronic Kidney Disease Epidemiology Collaboration (CKDEPI) formula, the t1/2 biol via dosimetry. Patients were subdivided in groups with normal clearance (NC) (n = 37, 38.5%), medium clearance (MC) (n = 48, 50.0%), and low clearance (LC) (n = 11, 11.5%) (eGFR _ 90; 60-89; 15-59 ml/min per 1.73 m2, respectively). The relationship between eGFR and t1/2 biol of 131I was modeled using a power function. Results: The groups significantly differed in terms of age (NC 53.8, MC 68.6, and 78.0 years, respectively), serum creatinine levels (NC: 0.71; MC: 0.85; LC: 1.18 mg/dl), and t1/2 biol (NC: 0.53; MC: 0.71; LC: 1.01 days). The t1/2 biol was significantly influenced only by eGFR, and not by age, gender, or body weight. The relationship between t1/2 biol of 131I and eGFR was described by the formula t1/2 biol = 20.3 · eGFR−0.782. Conclusions: The calculated relationship between renal function and t1/2 biol of 131I can be used in principle to estimate a dose reduction for patients with renal insufficiency. The model, however, gives erroneous results in individual cases and therefore a routine utilization cannot be recommended. Prospective studies are necessary, based on larger patient numbers and more accurate methods for dose rate measurement and GFR.
Keywords: Renal insufficiency; Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI); thyroid cancer; radioiodine therapy; biological half-life; dose adaptation